2008
DOI: 10.1142/s0218271808012735
|View full text |Cite
|
Sign up to set email alerts
|

Relic Gravitational Waves and CMB Polarization in the Accelerating Universe

Abstract: In this paper we briefly present our works on the relic gravitational waves (RGW) and the CMB polarization in the accelerating universe. The spectrum of RGW has been obtained, showing the influence of the dark energy. Compared with those from non-accelerating models, the shape of the spectrum is approximately similar, nevertheless, the amplitude of RGW now acquires a suppressing factor of the ratio of matter over dark energy ∝ Ω m /Ω Λ ∼ 0.4 over almost the whole range of frequencies. The RGW spectrum is then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, as pointed out in [32,89], this may not be the case when the collapse dynamics is also taken into account. We now calculate the CSL contribution to the evolution ofR 2 during the radiation-dominated era, which lasts from time η e to η r ¼ 3 × 10 60 M −1 P which is estimated by using the fact that aðη r Þ=aðη e Þ ≈ 3 × 10 26 [90]. Notice that, as a first approximation, we are not including effects due to the reheating stage [90], and directly consider the radiation-dominated era as following the inflationary one.…”
mentioning
confidence: 99%
“…However, as pointed out in [32,89], this may not be the case when the collapse dynamics is also taken into account. We now calculate the CSL contribution to the evolution ofR 2 during the radiation-dominated era, which lasts from time η e to η r ¼ 3 × 10 60 M −1 P which is estimated by using the fact that aðη r Þ=aðη e Þ ≈ 3 × 10 26 [90]. Notice that, as a first approximation, we are not including effects due to the reheating stage [90], and directly consider the radiation-dominated era as following the inflationary one.…”
mentioning
confidence: 99%
“…(5) has been solved by perturbations, yielding the full analytic solution h k (η), from the inflation up to the present accelerating stage [14,19], and it has been found that the relativistic freestreaming gas causes a damping of h k by ∼ 20% in the frequency range ν ≃ (10 −16 , 10 −10 )Hz. The RGWs can generate the CMB temperature and polarization anisotropies power spectra C XX ′ ℓ (XX ′ = T T, T E, EE, BB), by the Sachs-Wolfe effect [13,14,24,25,26,27,28,29,30,31,32]. As shown in Ref [14], the mode functions h k (η d ) andḣ k (η d ) at the photon decoupling time η d , i.e.…”
Section: Effects Of Free-streaming Gas On Rgws and Cmb Polarizationsmentioning
confidence: 99%
“…There are several works in the field that extracted an analytical expression for the C XX , in a flat universe such as Refs. [5,6,7,8,9,10,11] where all analytical spectra have been extracted by considering the tensor perturbation as a source. Ref.…”
Section: Introductionmentioning
confidence: 99%